The Effect of Dexmedetomidine on the Acute Pain After Cardiothoracic Surgeries: A Systematic Review - Habibi, Valiollah; Kiabi, Farshad Hasanzadeh; Sharifi, Hassan (Revista brasileira de cirurgia cardiovascular, 2018)
Acute post-operative pain remains a troublesome complication of cardiothoracic surgeries. Several randomized controlled trials have examined the efficacy of dexmedetomidine as a single or as an adjuvant agent before, during and after surgery. However, no evidence-based conclusion has been reached regarding the advantages of dexmedetomidine over the other analgesics. To review the effect of dexmedetomidine on acute post-thoracotomy/sternotomy pain. Medline, SCOPUS, Web of Science, and Cochrane databases were used to search for randomized controlled trials that investigated the analgesia effect of dexmedetomidine on post-thoracotomy/sternotomy pain in adults' patients. The outcomes were postoperative pain intensity or incidence, postoperative analgesia duration, and the number of postoperative analgesic requirements. From 1789 citations, 12 trials including 804 subjects met the inclusion criteria. Most studies showed that pain score was significantly lower in the dexmedetomidine group up to 24 hours after surgery. Two studies reported the significant lower postoperative analgesia requirements and one study reported the significant lower incidence of acute pain after surgery in dexmedetomidine group. Ten studies found that the total consumption of narcotics was significantly lower in the dexmedetomidine group. The most reported complications of dexmedetomidine were nausea/vomiting, bradycardia and hypotension. Dexmedetomidine can be used as a safe and efficient analgesic agent for reducing the postoperative pain and analgesic requirements up to 24 hours after cardiothoracic surgeries. However, further well-designed trials are needed to find the optimal dosage, route, time, and duration of dexmedetomidine administration.